The effect of the COVID-19 induced uncertainty on the Canadian economy - El Mansouri, Mouad (Université d'Ottawa | University of Ottawa, 2020)
One of the most challenging factors that is characterizing the current economic crisis is the COVID-19 induced uncertainty. Policymakers and economists play a crucial role in implementing an effective and accommodative economic policy that would be able to soften the blow caused by this notorious virus. The aim of this paper is to estimate the impact of COVID19’s uncertainty on the Canadian real economy through the use of a Structural Vector Autoregressive model with exogenous variables (SVARX). To the best of our knowledge, no other study attempted to achieve the same objective. This paper demonstrates that the Canadian real economy will experience a significant slowdown due to the Covid-19 uncertainty as shown through the fall of the Canadian GDP. The inflation rate will be subjected to some deflationary pressures following the unexpected shock. Last but not least, the Bank of Canada will be expected to decrease its overnight interest rate in order to support the economic recovery.